Uwarunkowania konkurencyjności uprawy buraka cukrowego w Polsce w obliczu reformy rynku cukru - Karpińska, Joanna; Kraużlis, Milda (Conditions for Competitiveness Sugar Beet Cultivation in Poland in the Wake of the EU Sugar Market Reform, 2006)
Sugar beet has always been an important element of agro-food industry. The plant requires high culture cultivation and very good soil quality. Sugar beet yields good harvests in favorable climatic conditions, and gives growers satisfaction and profits. Polish sugar beet growers were satisfied with the price obtained after the European Union accession. As a result, they were more willing to buy delivery rights that would guarantee satisfactory and stable income. From the 1 July 2006 a new European sugar market regulation will take effect. There are many fears connected with the uncertainty of the reform. The most controversial is the aim of the reform - decreasing of the sugar production by prices reduction. Despite the guarantees to compensate the lost income, farmers are awaiting the changes with concern. A restructuring fund offered to sugar producers is the main argument used by fanners that the sugar production volume will definitely diminish. Besides, there is an extensive research of the alternative usage of sugar is now going on. The best known example is bio-fuel. Poland is the third largest producer of sugar in the EU and fifth in Europe. In the near future under the new sugar market organization Poland will switch from being a sugar exporter into a sugar importer.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 379-385